PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN DI BEI - Rofina WPPW, Maria Rofina WPPW (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
Good Corporate Governance (GCG) is a system which regulates the relation among variousinterested parties (stakeholders) in order to achieve the company objectives. Good Corporate Governance(GCG) is performed in order to keep the company under the control of strong and discipline managementas well as to prevent the occurrence of disorders which can be improved immediately. Therefore, thisresearch is meant to find out the implementation influence of Good Corporate Governance (GCG) to thefinancial performance of companies which are listed in the Indonesia Stock Exchange. The purposivesampling is applied in this research as the sample selection technique which is applied on the companieswhich are listed in the Indonesia Stock Exchange which follows the survey of the Indonesian Institute forCorporate Governance and achieving the best rank in 2006 â 2011. The hypothesis test is performed byusing the simple linear regression analysis with statistic analysis in the form of t statistic test. The result ofthe research indicates that the partial implementation of good corporate governance has an influence tothe net profit margin, the implementation of good corporate governance has an influence to the return oninvestment, and the implementation of good corporate governance has an influence to the return onequity.Keywords: Good Corporate Governance (GCG), Return On Investment (ROI), Net Profit Margin (NPM),Return On Equity (ROE).